Colloquium and General Meeting Trackless Mining in Underground Metal Mines (The Southern African Institute of Mining and Metallurgy)
Colloquium And General Meeting - Trackless Mining in Underground Metal Mines A General Meeting and Mining Colloquium on the above topic was held on Wednesday, May 16th, 1973, at Kelvin House. Dr J. P. Hugo (President) was in the chair. The colloquium wasattended by approximately 200 delegates, and was opened by the President at 9.15 a.m. OBITUARIES The President: It is my sad duty to announce the death of the following: W. A. Schwezoff and L. G. S.